AutoPot: An Innovative Urban Gardening with IoT-enabled Watering System - Mohd Hanifa, Rafizah; Suderman, Muhammad Haiqal; Hamsan, Hanis Nabihah; Amran, Shaza Batrisyia (Multidisciplinary Applied Research and Innovation, 2025)
Urban living environments such as condos, apartments, flats, and otherhigh-rise buildings often lack personal garden spaces, compellingresidents to grow plants in pots. Residents who cultivate plants in potsencounter difficulties in regulating watering routines, necessitatingirrigation during dry weather while refraining from watering duringhumid weather. This can be particularly difficult for those with busywork schedules. Therefore, there is a need for an automated wateringsystem to assist them in maintaining optimal soil moisture levelswithout the constant need for manual intervention. The AutoPot isproposed to address this gap by developing a prototype that leveragesIoT technology to optimize watering practices. The AutoPot integratessensors to monitor soil moisture, humidity, and temperature levels inreal-time, automatically activating a water pump when the soil moisturedrops below a preset threshold. This study evaluates the AutoPotsystem based on its efficiency in watering plants by monitoring soilmoisture levels. The system's performance is assessed by its ability tomaintain optimal soil moisture, ensuring plants receive adequate waterwithout over- or under-watering. Data collected at regular intervalsdemonstrate that the AutoPot successfully maintains soil moisture,humidity, and temperature within desired ranges. Future work willexplore adaptive algorithms that adjust watering schedules based onsoil type, plant species, and growth stages to further optimize waterusage and plant health.